Congo Red Decolorization Using Textile Filters and Laccase-Based Nanocomposites in Continuous Flow Bioreactors - Natalia Lopez-Barbosa; Sergio Leonardo Florez; Juan C. Cruz; Nancy Ornelas-Soto; Johann F. Osma (Nanomaterials, 2020)
Removal of azo and diazo dye content from textile industry wastewaters is crucial due to their environmental impact. Here, we report on the use of the fungal laccase from Pycnoporus sanguineus CS43 immobilized on silica nanoparticles and entrapped in textile-based filters for the degradation of Congo Red. Laccase immobilization and synthesis of the nanocomposites were carried out by two different methods, one in the presence of acetone and the second using water as solvent. This led to a change in the hydrophobicity of the obtained biofilters. Successful preparation of the nanocomposites was confirmed via FTIR spectroscopy. Changes in the secondary structure of the enzyme were inspected through the second derivative of the FTIR spectra. Six different types of filter were fabricated and tested in a continuous flow bioreactor in terms of their decolorization capabilities of Congo Red. The results indicate removal efficiencies that approached 40% for enzymes immobilized on the more hydrophobic supports. Backscattered electron (BSE) images of the different filters were obtained before and after the decolorization process. Percentage of decolorization and activity loss were determined as a function of time until a plateau in decolorization activity was reached. Experimental data was used to recreate the decolorization process in COMSOL Multiphysics® (Stockholm, Sweden). These simulations were used to determine the proper combination of parameters to maximize decolorization. Our findings suggest that the treatment of textile-based filters with immobilized laccase in conjunction with hydrophobic nanocomposites provides a suitable avenue to achieve more efficient laccase dye decolorization (39%) than that obtained with similar filters treated only with free laccase (8%). Filters treated with silica-based nanocomposites and immobilized laccases showed an increase in their decolorization capability, probably due to changes in their wetting phenomena.